2020
DOI: 10.1088/2053-1591/ab6c63
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity, morphology, and physicochemical stability of biosynthesized silver nanoparticles using thyme (Thymus vulgaris) essential oil

Abstract: Considering the importance of biosynthesized silver nanoparticles (AgNPs) using plant phytochemicals, the aim of this work was to evaluate the effect of pH in the formulation of AgNPs, bioreduced with thyme essential oil. Biosynthesized AgNPs were prepared under different pH (7, 8, 9 and 10), and the physicochemical stability was evaluated during 90 days at 6°C and 25°C. Using GC/MS technique, 17 different compounds were observed in the thyme essential oil; however, borneol and αterpineol were the majoritarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
1
13
0
5
Order By: Relevance
“…Based on our results, we have recommended to obtain a circumspect selection of the green extracts used for the synthesis of nanoparticles, and suggested that a comprehensive screen of the products should be carried out prior to their applications to delineate their behavior in the presence of living systems. Based on today’s nanotechnology results, combining the available methods of biology, chemistry and material sciences, more complex investigations can be carried out [ 162 , 163 ]. Using such an approach, systematic examinations regarding AgNP aggregation behavior with simultaneous measurements of its effect on biological activity can be performed to offer new frontiers to preserve nanoparticle toxicity by enhancing colloidal stability [ 70 ].…”
Section: Synthesismentioning
confidence: 99%
“…Based on our results, we have recommended to obtain a circumspect selection of the green extracts used for the synthesis of nanoparticles, and suggested that a comprehensive screen of the products should be carried out prior to their applications to delineate their behavior in the presence of living systems. Based on today’s nanotechnology results, combining the available methods of biology, chemistry and material sciences, more complex investigations can be carried out [ 162 , 163 ]. Using such an approach, systematic examinations regarding AgNP aggregation behavior with simultaneous measurements of its effect on biological activity can be performed to offer new frontiers to preserve nanoparticle toxicity by enhancing colloidal stability [ 70 ].…”
Section: Synthesismentioning
confidence: 99%
“…The average zeta potential values were found to be ‐31.4 ± 1.04 mV and ‐30.3 ± 086. mV for nAg‐IAA and nAg‐IBA, respectively which show the stable colloidal structure of the nanoparticles (Figure 2B). [ 21,22 ]…”
Section: Resultsmentioning
confidence: 99%
“…Alguns grupos funcionais dos óleos podem interagir com diferentes íons, formando ligações que favorecem o processo de nucleação de NPs. MELO et al [30] explicaram o mecanismo de biossíntese de AgNPs com óleo essencial de tomilho (Thymus vulgaris). Segundo os autores, a reação de redução de Ag + em Ag 0 ocorreu pela doação de prótons H + do borneol (composto de maior concen-tração encontrado no óleo essencial), com a estabilização simultânea do borneol pelo sódio (Na + ) da solução percursora.…”
Section: Biossínteses Mediadas Por óLeos Essenciaisunclassified
“…A ação redutora do óleo essencial de tomilho (Thymus vulgaris) foi aplicada na síntese de AgNPs, que foi avaliada por sua atividade antibacteriana contra Escherichia coli e Staphylococcus aureus [30]. As nanopartículas apresentaram formato esférico com tamanho médio de 90 nm, e pico de absorbância entre 415 e 440 nm.…”
Section: Biossínteses Mediadas Por óLeos Essenciaisunclassified
See 1 more Smart Citation